Analisis Risiko Penerapan Warehouse Management System pada Proses Inbound di Gudang Cold Storage - Maulana, Andy; Pratiwi, Sekar Widyastuti; Emyus, Achmad Maulizal Sutawijaya; Aulia, Bestyas Pratiwi; Jayasakti, Reza Fauzi; Kania, Dinar Dewi (Jurnal Sistem Transportasi & Logistik, 2022)
PT XYZ is a company engaged in logistics, such as providing goods distribution and consolidation services for Export, Import, Cargo Transportation, Customs Clearance, Halal Logistics & Cold Storage, Warehouse and Freight Forwarder activities. One of the services provided is Cold Storage. The warehouse serves the storage of several customers in good finish storage. This research is motivated by the findings of field studies that in the process of inbound goods in cold storage warehouses using the Warehouse Management System (WMS) obstacles arise which cause the inbound process to be hampered and not run smoothly, these factors appear and become a risk. So it is necessary to do risk management or risk analysis. The analysis will identify risk, assess risk and accept risk. The results of the risk obtained in the inbound process of goods in the cold storage warehouse using the Warehouse Management System (WMS) from the identification that there are 5 (five) risks that arise in these activities, there are 2 (two) risks that are included in the Acceptable category and 3 (three) types of risk with the Undesirable category (unexpected) so that mitigation is needed to minimize the impact of the identified risks. Based on the results of the research that has been carried out, it can explain the theories, concepts and analytical methods used, and can provide an overview in the process of qualitative risk analysis.